INVESTIGATING THE TREND OF POPULATION GROWTH IN AKWA IBOM STATE USING GENERALIZED LINEAR MODELS - Loko, Ibrahim; Adenomeon, Monday Osagie; Udott , Patience Friday; Musa, Saleh Ibrahim (Top Journal of Public Policy and Administration (TJPPA), 2025)
This study investigated the trend of population growth in Akwa Ibom using generalized linear models. Annual population growth data were collected from the National Population Commission for the period of 2006 to 2023. The calculated natural increase revealed a positive trend in the natural increase in akwa ibm from 2006 to 2023. Evidence from summary statistics revealed some degree of over-dispersion (variance > mean). This study explored Poisson and Negative Binomial Regression Models using two links (identity and log). The results revealed a significant positive increase in population growth in the state among the models. Overall, negative binomial regression with identity link for population growth rate was superior among the competing models. Therefore, Data on numbers of population growth are essential if states are to determine priorities, develop and monitor policies for public health care, as well as other government policies that may be based on such data